Plastik Sanatlar Alanında Resim Sanatçı Seçkileri-1 - Keleş, Nurgül; Alioğlu, Hamid Maharramov; Erol, Songül Esin; Özmen, Ahmet Fatih; Eren, Abdurrahman; Sevindik, İlyas and Gezen, Mehmet Cihan and Özçelikçi Taşören, Birgül and Büyükparmaksız, Mehmet Ali (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-